Estrus detection, first service conception, and embryonic death in beef heifers synchronized with MGA and prostaglandin - G.C. Lamb; B.L. Miller; V. Traffas; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1997)
In April, 1996, 1501 yearling crossbred heifers located on seven different ranches were estrus-synchronized and artificially inseminated (AI) 12 hours after they were detected in estrus. Herd size ranged from 82 to 43 9 head. Of the 1501 heifers, 86.1% were detected in estrus. First service conception rates of those 1292 heifers averaged 58.4% (40.3 to 68.8%). In three herds, ultrasonography was used to diagnose 525 heifers as pregnant at 30 days after AI. At 60 to 90 days after the breeding season, palpation of the uterus confirmed that embryonic death had occurred in 4.2% (4.0 to 4.8%). First service conception rates varied widely among ranches. The variation might have been due to factors such as climate, average daily gain, body condition, A I technician, and AI sire. A small percentage of embryos died after the 30-day ultrasound exam regardless of the ranch or management system.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Artificial insemination; Synchronization; Ultrasound; Conception; Embryonic death